2011
DOI: 10.1586/era.10.217
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose radiation therapy of cancer: role of immune enhancement

Abstract: The efficacy of conventional radiation therapy, one of the most widely used treatment modalities of cancer, is limited by resistance of tumors as well as normal tissue toxicity. In the last decade, several studies have shown that protocols using low-dose radiation (LDR) are more effective in providing local tumor control with negligible normal tissue toxicity. LDR stimulates antioxidant capacity, repair of DNA damage, apoptosis and induction of immune responses, which might be collectively responsible for prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 91 publications
5
57
0
3
Order By: Relevance
“…Although LDR was also considered dangerous according to the linear no-threshold (LNT) hypothesis (32), increasing evidence has suggested that LET radiation at dose levels Ͻ100 mGy could induce beneficial effects, including extending life span, enhancing immunity, and improving DNA repair (17,23,36). Epidemiological surveys have analyzed individuals exposed to Ͻ100 mGy radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although LDR was also considered dangerous according to the linear no-threshold (LNT) hypothesis (32), increasing evidence has suggested that LET radiation at dose levels Ͻ100 mGy could induce beneficial effects, including extending life span, enhancing immunity, and improving DNA repair (17,23,36). Epidemiological surveys have analyzed individuals exposed to Ͻ100 mGy radiation.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to this end is the identification of adjuvants that can increase the effectiveness of current therapies [4][5][6][7]. Ideally, an adjuvant should be non-toxic, easy to administer and have known pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…adverse side effects (Sakamoto, 2004;Farooque et al, 2011). Several retrospective human studies have shown a reduced cancer incidence from low dose radiation, however such studies are subject to many confounding factors, and so they are not discussed here.…”
Section: Shifting the Paradigm In Radiation Safetymentioning
confidence: 99%